Contribuições da teoria do amadurecimento de D. W. Winnicott para o atendimento socioeducativo ao adolescente privado de liberdade - Rocco, Cláudia (2010)
This research aims to show possibilities and ways to build a model of socialeducational enforcement for adolescents who are an offender, under the regime of deprivation of liberty, based on the theory of emotional maturing of Donald Woods Winnicott. The theoretical understanding combined with the experience accumulated during the last six years providing psychological treatment for adolescents in internal unit of the Foundation CASA - Adolescent Socio-educational Enforcement Center - São Paulo / SP, prompted reflections on the value of Winnicott's ideas for the development of a model of social-educational enforcement. We contextualize the social place of adolescents and interventions targeted at children and teenagers by emphasizing the paradigm changing: the Doctrine of Irregular Situation to the Doctrine of Integral Protection who now directs the social-educational enforcement in the country and the state of São Paulo. The presentation of the life history and institutional life of a teenager girl who abide by social care into an CASA Foundation unit / SP and to study her case in light of Winnicott's theory show that the Winnicott s Maturing Theory provides the information necessary for future construction of a model of social-educational enforcement that can be implemented in units of the CASA Foundation / SP and / or in the Brazilian context in institutions that meet adolescents with a court decision to under admission an internal socio-educational measure in educational establishment